DROUGHT TOLERANT INDICES OF LOWLAND TOMATO CULTIVARS - Amalia Tetrani Sakya; Endang Sulistyaningsih; Benito Heru Purwanto; Didik Indradewa (Indonesian Agency for Agricultural Research and Development, 2020)
The released lowland tomato cultivars are known for their resistance to plant diseases and high temperatures. The study aimed to identify the drought tolerance of lowland tomato cultivars based on the drought tolerant indices. The study was arranged in a split plot design, using seven lowland tomato cultivars (Zamrud, Permata F1, Ratna, Mirah, Tombatu F1, Tyrana F1, and Tymoti F1) as the main plot and watering (standard conditions and once every eight days as the drought conditions) as the subplot. Parameters observed were morpho physiological characters (plant height, leaf area, biomass, root length, root surface area, shoot root ratio, relative moisture content, membrane stability index, chlorophyll levels, and proline levels). The parameters observed in each character included the sensitivity stress index (SSI), stress tolerance index (STI), and yield stability index (YSI). Results showed that four cultivars (Tyrana F1, Tymoty F1, Mirah, and Tombatu F1) were drought tolerance, and three cultivars (Ratna, Permata F1, and Zamrud F1) were susceptible. The water stress decreased agronomic and physiological traits performance, but the drought-tolerant cultivars were less affected to the stress and produced higher fruit weight. The study implies that the drought-tolerant cultivars could be used as a promising source for drought tolerant genotypes.